Predictive Value of Dynamic Changes in Hemoglobin Levels During Early Pregnancy for the Development of Anemia During Pregnancy - Liu L; Li X (International Journal of Women's Health)
Lulu Liu,1 Xiaoqing Li2 1Department of Anesthesiology, Tongzhou Maternal and Child Health Hospital, Beijing, 101100, People’s Republic of China; 2Department of Obstetrics, Tongzhou Maternal and Child Health Hospital, Beijing, 101100, People’s Republic of ChinaCorrespondence: Xiaoqing Li, Email 15116980204@163.comBackground: Anemia affects over 30% of pregnancies globally and is associated with adverse maternal-fetal outcomes, underscoring the critical need for early risk prediction.Objective: This study aimed to assess the predictive value of early pregnancy hemoglobin levels for anemia development in mid- and late pregnancy.Methods: We conducted a retrospective cohort analysis of 1999 singleton pregnancies with neuraxial labor analgesia at Beijing Tongzhou District Maternal and Child Health Hospital (January 2022–January 2023). Inclusion criteria included age ≥ 18 years, BMI 19.0– 44.3 kg/m², and ASA II classification. Exclusions comprised multifetal gestations, chronic hematologic disorders, or incomplete data. Hemoglobin trends were analyzed using Sankey diagrams, and predictive thresholds were determined via ROC curves (R 4.4.1).Results: The cohort included 76.94% primiparas and 45.47% with comorbidities (hypertension, diabetes, thyroid disorders). Hemoglobin levels declined significantly from early pregnancy (median 131.00 g/L) to mid- and late pregnancy (118.00 g/L; P< 0.001). ROC analysis identified early-pregnancy hemoglobin thresholds for anemia prediction: < 126.5 g/L (mid-pregnancy AUC 0.82, 95% CI 0.80– 0.84) and < 127.5 g/L (late-pregnancy AUC 0.71, 95% CI 0.68– 0.74).Conclusion: Early pregnancy hemoglobin thresholds provide a clinically actionable tool for identifying high-risk pregnancies, enabling timely interventions to reduce anemia-related complication.Keywords: early pregnancy, hemoglobin, anemia, ROC curve, predictive efficacy